Analisis Efektivitas Metode Filtering dan Intersection dalam Analisis Data Permukaan Bangunan dengan QGIS - Nandana, Prana Wijaya Pratama; Faisal, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2025)
This study evaluates the efficiency of two methods for processing geospatial building surface data, namely Filtering and Intersection, using a case study in Blitar Regency. The data for this research was obtained by comparing two sources: OpenStreetMap (OSM), which has a data completeness rate of 60%, and Google Open Building, with a data completeness rate of 90%. From these two sources, the data with the highest completeness, which is from Google Open Building, was selected for further analysis. The data processing was carried out using QGIS software, chosen for its capability to support various geospatial analysis methods. The comparison of the two methods was based on three main criteria: processing time, resource efficiency, and scalability. The results showed that the Filtering method outperforms in all these aspects. Filtering can complete processing in an average of 1.6 seconds, significantly faster than the Intersection method, which requires an average of 7 minutes and 50 seconds. In terms of resource efficiency, Filtering is also more economical, with an average CPU usage of 18.85% and memory usage of 121.4 MB, compared to the Intersection method’s 34.05% CPU usage and 236.4 MB of memory. Additionally, the Filtering method demonstrated better scalability, capable of handling larger datasets with fewer resources and less time. Therefore, the Filtering method is recommended for geospatial data processing that prioritizes speed, efficiency, and the ability to handle large and complex datasets.